profile
Опубликовано - 1 месяц назад | По предмету Математика | автор Аноним

Помогите решить 2√3×√2×8√6

  1. Ответ
    Ответ дан Михеева Галина
    2 * √3 × √2 × 8 * √6 = 2 * √( 3 * 2) × 8 * √6 = 2 * √6 × 8 * √6 = 2 * √( 6 * 6 ) × 8 = 2 * √36 × 8 = 2 * 36 ^ ( 1 / 2 ) × 8 = 2 * ( 6 ^ 2 ) ^ ( 1 / 2 ) * 8 = 2 * 6 ^ ( 2 * 1 / 2 ) * 8 = 2 * 6 ^ ( 2 / 2 ) * 8 = 2 * 6 ^ 1 * 8 = 2 * 6 × 8 = 12 * 8 = ( 10 + 2 ) * 8 = 10 * 8 + 2 * 8 = 80 + 2 * 8 = 80 + 16 = 96 ;
    В итоге получили, 2 * √3 × √2 × 8 * √6 = 96;
    Ответ: 2 * √3 × √2 × 8 * √6 = 96.
    0